LATIN AMERICAN CONSTITUTIONAL LAW: INTEGRATION FROM THE DIALOGUE BETWEEN NATIONAL AND INTERNATIONAL LEGAL SYSTEMS - Luiz, Conci Guilherme Arcaro (Anales Universitatis Apulensis Series Jurisprudentia, 2013)
ABSTRACT There is a constitutional identity in Latin America, which is based primarily on constitutional context approximate, with features like hyperpresidentialism, weak state institutions of control, such as the judiciary and the legislature co-opted, and large periods of authoritarianism,  corruption of officials, among others. From the 1980s, starts on the mainland, a period of democratization, with new constitutions (Brazil, Venezuela, Colombia, Peru, Chile, etc..) and refurbishment of existing (Mexico and Argentina). Among the changes made, there is a process of opening the constitutions for the international law of human rights, the strengthening of the institutions of the Organization of American States (OAS). Regarding the Inter-American Court of Human Rights, this becomes more activist, and creates a doctrine called the doctrine of control of conventionality which requires not only the Court itself but the judges of national states to control the validity of national acts (laws , administrative acts, judicial decisions, constitutions) on the grounds of the American Convention of Human Rights(ACHR) and also about the interpretation given by the Court itself about the ACHR . This process of legal integration is thus awarded a new actor, which produces a deepening of a ius constitucionale commune . In my paper and conference, I will discuss this process and the effects of this dialogue between legal systems, especially the courts in the continent. Words: Integration. Human Rights. Dialogue. Control of conventionality. Latin American Constitutional Law